Chlorpromazine and Posthypertonic Stress as Model of Damage in Cryopreserved Cells During Thawing - Chabanenko, Olena O.; Semionova, Ekateryna A.; Shpakova, Natalia M. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):161.